Observing primary literacy - Perkins, Margaret (Sage Publications Ltd., 2012)
"Observing children is a fundamental aspect of learning to teach and a vital component of primary English teaching. Observing Primary Literacy focuses on observing children and teachers in elementary classrooms. Its purpose is to enable students to make sense of what they observe in classrooms. This book aims to help make explicit the reasons for the professional decisions teachers make before and during lessons, as well as encouraging critical and reflective thought on key aspects of primary English. Using a detailed examination of real-life case studies, Margaret Perkins provides a framework for understanding the literacy learning processes of elementary-age children and how this can inform good teaching practice. She demonstrates to readers how to re-focus on children's learning and develop a critically informed approach to literacy in the modern classroom."--Publisher's website.